I would have given my approach but i didnt get anywhere. I just substituted zeroes and got $f(f(n)) =n$ and I'm just lost. Any help would be appreciated

  • 4
    $\begingroup$ Is $0$ natural number? $\endgroup$
    – nonuser
    Jun 23, 2019 at 11:18

2 Answers 2


Solution 1. assuming $0\in\mathbb{N}$

Note that $f$ is clearly injective, so if we substitute $n=0$ we find that $f(m^2+f(0))=f(m^2)$, from which we see that by injectivity that $f(0)=0$. Letting $m=0$ in the original equation, we see that $f$ is indeed an involution as OP found.

Then if we set $m=1$ and $n=f(n)$, we find that $f(n+1)=f(n)+f(1)$. A simple induction shows that $f(n)=nf(1)$ for all $n\in\mathbb{N}$, and so $f(n)=nc$ for some constant $c$.

Substituting this into our original equation, we find $c^2=1$, and after checking, we see that $f(x)=x$ is the only solution to the functional equation. ($c\in\mathbb{N}$, and so is not negative)

Solution 2. assuming $0\notin \mathbb{N}$

Note that when we put in $m=1$, we find that $$f(f(n)+1)=n+1\tag{1}$$ Setting $n=f(n)+1$ in $(1)$ shows that $$\begin{align*} f(f(f(n)+1)+1)&=f(n)+2 \\ \implies f(n+2)=f(n)+2 \tag{2}\end{align*}$$We now prove that $f(1)=1$. Suppose not, i.e. $f(1)=k$ for some integer $k>1$. Then $k-1\in\mathbb{N^+}$. So putting $n=k-1$ in $(2)$ shows that $f(k+1)=f(k-1)+2$. But if we put $n=1$ in $(1)$, we find that $$f(k+1)=f(f(1)+1)=2$$ which implies that $f(k-1)=0$, a contradiction. Hence $k=1\implies f(1)=1$. Hence $f(2)=2$, and a simple induction using $(2)$ shows that $f(n)=n$ for all $n\in\mathbb{N^+}$.


Assume $0 $ is an element of $\mathbb N$. Set $f(0) = N$. Taking $m=0$ we see $$ ff(n) = N + n $$ Now take $n=0$ in the original equation, we get a second identity $$f(m^2 + N) = f(m^2)$$

Apply $f$ to both sides to see (using first identity), $$ m^2 + 2N = N + m^2$$ Taking $m=0$ implies $N=0$. So now we know $ff(n) = n$. This implies $f$ is bijective. Suppose $f(M)=1$. Then $$ f(m^2 + 1) = f(m^2) + M$$ so we have $$ f(0)=0\\ f(M) = 1\\ f(1) = M $$ Now $f(2) = f(1^2+f(M))=f(1^2)+M = 2M$, and therefore $$ f(2) = 2M \\ f(2M)=2 \\ $$ Now $f(3)=f(1^2+f(2M))=f(1^2) + 2M = 3M$, and therefore $$ f(3)= 3M\\ f(3M)=3.$$ Inductively we obtain $$ f(M)=M^2 \\ f(M^2)=M$$ so $M$ solves $M^2=1$ i.e. $M=1$, and $f(n)=n$ for all $n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.